Historia w listach zaklęta. Korespondencja w Archiwum domowym Adeli Korczyńskiej (PDF 2,89 MB) (Książnica Śląska, 2025)
Adela Korczyńska was a teacher and scout. For many years she collected materials on women’s underground activities during WorldWar II. These materials currently form her home archive, storedin the Silesian Library. The article discusses a collection of correspondence and divides it into different themes such as private letters,letters related to the collector’s documentary work, original war correspondence (camp letters and secret messages), as well as letters related to the preparation and publication of her texts. It is a fascinatingaddition to Adela Korczyńska’s biography, revealing her wide circleof friends and acquaintances while providing valuable informationabout her workshop and methods of work. It also serves as a reminder of the remarkable life of a woman who dedicated herself to documenting the heroic actions of Girl Scouts during the dramatic yearsof World War II.